Dysregulation of lncRNA TFAP2A‐AS1 is involved in the pathogenesis of pulpitis by the regulation of microRNA‐32‐5p - Mingming Liu; Weijing Jia; Lin Bai; Qiaolin Lin (Immunity, Inflammation and Disease)
Abstract Objective This study was designed to evaluate TFAP2A‐AS1 expression in the dental pulp of teeth with or without pulpitis and to determine the function of TFAP2A‐AS1 in pulp cells. Methods GSE92681 was analyzed to filter out differentially expressed lncRNAs. Pulp samples from teeth with pulpitis and healthy teeth (control) were examined using real‐time (RT) quantitative polymerase chain reaction (qPCR). Human dental pulp stem cells (hDPSCs) were cultured in a specific medium for osteogenic induction, or treated with lipopolysaccharide (LPS) to simulate inflammation. The viability and apoptosis of human DPSCs (hDPSCs) were determined by XTT assay and apoptosis detection kit. Inflammation was induced by LPS and assessed by measuring the expression and release of inflammatory cytokines after TFAP2A‐AS1 knockdown. Osteogenic differentiation of hDPSCs was investigated by determining expression levels of osteogenic markers and alkaline phosphatase (ALP) activity after TFAP2A‐AS1 overexpression. The downstream microRNA (miRNA) was predicted. Dual‐luciferase reporter was used to confirm the binding between miR‐32‐5p and TFAP2A‐AS1. Results The expression of TFAP2A‐AS1 was evaluated in inflamed pulp using RT‐qPCR. TFAP2A‐AS1 had a discriminatory ability for healthy individuals and patients with pulpitis. The expression of TFAP2A‐AS1 decreased upon the osteogenic differentiation of hDPSCs, and increased upon the LPS induction. TFAP2A‐AS1 can reverse the osteogenic differentiation of hDPSCs, as evidenced by decreased levels of dentine sialophosphoprotein, dentin matrix protein−1, and ALP activity. TFAP2A‐AS1 knockdown can promote cell proliferation of hDPSCs and relieve LPS‐induced inflammation, as evidenced by decreased levels of TNF‐α, IL‐1β, and IL‐6. miR‐32‐5p was identified as a downstream miRNA of TFAP2A‐AS1. Conclusion This study demonstrated the expression and potential function of TFAP2A‐AS1 in the human dental pulp. TFAP2A‐AS1 can inhibit odontogenic differentiation but promote inflammation in pulp cells.